The effect of single-cell knockout of Fragile X Messenger Ribonucleoprotein on synaptic structural plasticity - Gredell, Marie; Lu, Ju; Zuo, Yi (Frontiers in Synaptic Neuroscience, 2023)
Fragile X Syndrome (FXS) is the best-known form of inherited intellectual disability caused by the loss-of-function mutation in a single gene. The FMR1 gene mutation abolishes the expression of Fragile X Messenger Ribonucleoprotein (FMRP), which regulates the expression of many synaptic proteins. Cortical pyramidal neurons in postmortem FXS patient brains show abnormally high density and immature morphology of dendritic spines; this phenotype is replicated in the Fmr1 knockout (KO) mouse. While FMRP is well-positioned in the dendrite to regulate synaptic plasticity, intriguing in vitro and in vivo data show that wild type neurons embedded in a network of Fmr1 KO neurons or glia exhibit spine abnormalities just as neurons in Fmr1 global KO mice. This raises the question: does FMRP regulate synaptic morphology and dynamics in a cell-autonomous manner, or do the synaptic phenotypes arise from abnormal pre-synaptic inputs? To address this question, we combined viral and mouse genetic approaches to delete FMRP from a very sparse subset of cortical layer 5 pyramidal neurons (L5 PyrNs) either during early postnatal development or in adulthood. We then followed the structural dynamics of dendritic spines on these Fmr1 KO neurons by in vivo two-photon microscopy. We found that, while L5 PyrNs in adult Fmr1 global KO mice have abnormally high density of thin spines, single-cell Fmr1 KO in adulthood does not affect spine density, morphology, or dynamics. On the contrary, neurons with neonatal FMRP deletion have normal spine density but elevated spine formation at 1 month of age, replicating the phenotype in Fmr1 global KO mice. Interestingly, these neurons exhibit elevated thin spine density, but normal total spine density, by adulthood. Together, our data reveal cell-autonomous FMRP regulation of cortical synaptic dynamics during adolescence, but spine defects in adulthood also implicate non-cell-autonomous factors.